Perancangan Interior Pusat Ekspresi Seni Pertunjukan Talenta Muda di Surabaya - Kevin Dwiputra Wahono; Sriti Mayang Sari; Linggajaya Suryanata (Intra, 2019)
Interior design of youth talent performing arts center has a purpose to be a place to express artistic expression that is different among other places. This design was made for young talents, especially in Surabaya. This design uses the design thinking method that contains six stages. The site used in this design is the Dyandra Convention Center that is located in the middle of the city to get the ease of access. In this design, the designer uses the concept “Passion of Synchronize Expression”, where there are many expressions in an art show, but it must be synchronized to become an interesting show. The performing arts center provides spaces that can be used from the preparation of a show (training, preparation of decorations, make up and dressing room) and even for producing a show that is watched by the general audience.